Racismo na "família ferroviária": brancos e negros na Companhia Paulista em São Carlos. - Ferreira, Lania Stefanoni (2004)
This research consists in a study of the relationship between white and black employees of the Companhia Paulista de Estrada de Ferro between 1930 and 1961. The aim of this research is to understand the racial relations between these two groups, how they formed their identity in everyday work and the forms of racial discriminations. To realise this research, twenty retired laborers of Companhia Paulista who live in São Carlos were interviewed.